2005
DOI: 10.3189/172756405781813500
|View full text |Cite
|
Sign up to set email alerts
|

Estimating alpine snowpack properties using FMCW radar

Abstract: Large variations in both snow water equivalent (SWE) and snow slope stability are known to exist in the alpine snowpack, caused by wind, topographic and microclimatic effects. This variability makes extrapolation of point measurements of snowpack properties difficult and prone to error, but these types of measurements are used to estimate SWE and stability across entire mountain ranges. Radar technology provides a promising alternative to point measurements, because large areas can be covered quickly and non-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 23 publications
2
43
0
Order By: Relevance
“…Many authors have used GPR to characterize alpine (Marshall et al, 2005;Bradford et al, 2009a;Heilig et al, 2010), arctic (Holmgren et al, 1998), and on-glacier (Macguth et al, 2006) snowpack. Studies on freshwater ice have demonstrated that GPR can profile lake ice (Arcone et al, 1997) and river ice (Arcone and Delaney, 1987) thickness.…”
Section: Field Area and Methodsmentioning
confidence: 99%
“…Many authors have used GPR to characterize alpine (Marshall et al, 2005;Bradford et al, 2009a;Heilig et al, 2010), arctic (Holmgren et al, 1998), and on-glacier (Macguth et al, 2006) snowpack. Studies on freshwater ice have demonstrated that GPR can profile lake ice (Arcone et al, 1997) and river ice (Arcone and Delaney, 1987) thickness.…”
Section: Field Area and Methodsmentioning
confidence: 99%
“…Using a sliding assembly, the antennas are moved over a short distance (less than 3 m) to obtain images of snowpack stratigraphy [Marshall et al, 2004]. Movement of the radar system enables a measurement of SWE to be made over a large area [Marshall et al, 2005]. The FMCW radar can also be set up to measure snowpack stratigraphy at a point location [Ellerbruch and Boyne, 1980].…”
Section: Radar Devicesmentioning
confidence: 99%
“…As a more thorough summary of previous FMCW radar work in snow has been given elsewhere (e.g. Marshall et al, 2004b), here we briefly indicate the major studies. Ellerbruch and Boyne (1980) were the first to publish results of FMCW measurements in alpine snow.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave FMCW radar responds to changes in dielectric properties within the snowpack, as major reflections have been shown to be highly correlated with changes in dielectric properties measured in situ in a nearby snowpit (Marshall et al, 2004b). Using metal reflectors inserted at layer boundaries, this study also showed that the major reflections often coincide with boundaries observed visually in a nearby snowpit, and that using the mean density to approximate the velocity of propagation leads to an error in the depth scale Copyright  2004John Wiley & Sons, Ltd. Hydrol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation